Volcanisme Permien Du Massif De Chougrane-El Had Des Bouhsoussène (Maroc Central, Maroc) - Boutsougame, Abdelaziz; Ouazzani, Hassane; El Hadi, Hassan; Eddif, Aâtika (European Scientific Journal, ESJ, 2016)
Permian volcanic Chougrane-El Had the Bouhsoussène complex (central Morocco), manifested primarily by volcanic rocks rhyodacites nature and basalt intercalated in the clay-greso-conglomeratic permian deposits. These are rocks texture in general microlitic to porphyry. Basalts consists of a primary paragenesis formed of plagioclase, pyroxene, olivine and quartz and a secondary mineral assemblage consisting of muscovite, calcite, chlorite and quartz. The rhyodacites show primary paragenesis formed of plagioclase, pyroxene and quartz and a secondary mineral assemblage consisting of calcite and sericite. Petrographic characteristics of these rocks are comparable to those of the Permian volcanic complex Khénifra and Tiddas- Sebt Ait Ikkou (Central Morocco). Area Chougrane-El Had the Bouhsoussène created on intracontinentale tear in the Asturian phase (Michard, 1976) recorded three volcanic episodes, two major eruptive episode and a third in vein deposit mode.